2020
DOI: 10.31580/apss.v6i3.1301
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Determinants of Job Search Intention Among Fresh Graduates for the Supply of Labour Force in the Digital Era

Abstract: This study aims at exploring the psychological determinants that influence job search intention among fresh graduates. Digital innovations have changed the employment landscape that allows people to have flexible job opportunities. Building from the theory of planned behaviour, job search attitude, subjective norms, self-efficacy and perceived behaviour control were predicted to have positive effect on job search intention. A survey was conducted and the results of the regression test show job search attitude,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…Second, the study result regarding the direct relationship between subjective norms and job-seeking intentions was unexpected in the context of a collectivistic country like Bangladesh, and conflicts with the findings of past studies, which reported that subjective norms are an influential predictor for job-seeking intentions in a collectivist culture (e.g., Yizhong et al, 2017; Zainal et al, 2020), suggesting that normative pressures are not always attributable to millennial job seekers in a similar manner.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, the study result regarding the direct relationship between subjective norms and job-seeking intentions was unexpected in the context of a collectivistic country like Bangladesh, and conflicts with the findings of past studies, which reported that subjective norms are an influential predictor for job-seeking intentions in a collectivist culture (e.g., Yizhong et al, 2017; Zainal et al, 2020), suggesting that normative pressures are not always attributable to millennial job seekers in a similar manner.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings strengthen the fact that the bottom-line belief of self-appreciation on employability, help students in facing job market realities during job search. When individuals perceive themselves highly employable, they undergo channelised self-efficacy and career planning, which ultimately leads to proper job search (Zainal et al, 2020;Berntson, 2008;Jackson and Wilton, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, on the one hand, university students’ job search behavior will rely on the help of their peers around them, and on the other hand, they will have a comparative psychology about the job search efforts of their peers, which motivates them to search for jobs. However, the current literature on factors influencing university students’ employment intentions focuses on psychological factors ( Fort et al, 2015 ; Zainal et al, 2020 ), individual characteristics ( Tae-hyun, 2016 ; Zhang, 2019 ; Xu, 2022 ), social capital ( Wei, 2009 ; Lee and Cha, 2014 ), school type ( Song and Yan, 2019 ; Liu et al, 2021 ), job market ( Li, 2022 ), and policy environment ( Wang and Xianglong, 2021 ), few studies have considered the influence of surrounding peers on university students’ employment intentions. Even if a few studies have taken into account the influence of peers on university students’ employment intentions, they are mostly qualitative analyses ( Zhang and Siqi, 2021 ), and there is little empirical analysis literature to accurately identify the peer effects existing in university students’ employment intentions.…”
Section: Introductionmentioning
confidence: 99%